Posterior mandibular tooth replacement using a porcelain-fused-to-metal adhesive bridge with sanitary and conical pontic designs: A case report - Alyssa Salsabila; Nathania; Setyawan Bonifacius (Indonesian Journal of Prosthodontic, 2026)
Posterior mandibular tooth loss can significantly impair masticatory function, occlusal stability, and overall quality of life. Among available treatment options, adhesive bridges offer a minimally invasive alternative that preserves tooth structure while restoring function. This case report describes posterior mandibular tooth replacement using a porcelain-fused-to-metal (PFM) adhesive bridge incorporating two different pontic designs, namely sanitary and conical pontics. A 50-year-old female patient presented with missing posterior mandibular teeth and complaints of discomfort during mastication. Clinical examination revealed a Kennedy Class III modification 1 condition with favorable abutment support. A conservative treatment plan was developed using a resin-bonded fixed dental prosthesis. Tooth preparation was performed within enamel, followed by impression procedures and laboratory fabrication. The pontic design was selected based on anatomical and hygienic considerations, with a sanitary pontic applied in one region and a conical pontic in another. Following coping try-in and evaluation of marginal fit and occlusion, final cementation was performed using dual-cure resin cement. Post-insertion evaluation demonstrated satisfactory function, stability, and esthetics, with good periodontal response. This case highlights that appropriate pontic design selection plays a crucial role in achieving functional efficiency, hygiene maintenance, and long-term success in adhesive bridge restorations.